EPA guidance on the quality of mental health services: A systematic meta-review and update of recommendations focusing on care coordination. Issue 1 (2020) - Gaebel, W.; Kerst, A.; Janssen, B.; Becker, T.; Musalek, M.; Rössler, W.; Ruggeri, M.; Thornicroft, G.; Zielasek, J.; Stricker, J.
Abstract: Background: The quality of mental health services is crucial for the effectiveness and efficiency of mental healthcare systems, symptom reduction, and quality of life improvements in persons with mental illness. In recent years, particularly care coordination (i.e., the integration of care across different providers and treatment settings) has received increased attention and has been put into practice. Thus, we focused on care coordination in this update of a previous European Psychiatric Association (EPA) guidance on the quality of mental health services. Methods: We conducted a systematic meta-review of systematic reviews, meta-analyses, and evidence-based clinical guidelines focusing on care coordination for persons with mental illness in three literature databases. Results: We identified 23 relevant documents covering the following topics: case management, integrated care, home treatment, crisis intervention services, transition from inpatient to outpatient care and vice versa, integrating general and mental healthcare, technology in care coordination and self-management, quality indicators, and economic evaluation. Based on the available evidence, we developed 15 recommendations for care coordination in European mental healthcare. Conclusions: Although evidence is limited, some concepts of care coordination seem to improve the effectiveness and efficiency of mental health services and outcomes on patient level. Further evidence is needed to better understand the advantages and disadvantages of different care coordination models.